Physiological Considerations to Support Podium Performance in Para-Athletes - Gee, Cameron M.; Lacroix, Melissa A.; Stellingwerff, Trent; Gavel, Erica H.; Logan-Sprenger, Heather M.; West, Christopher R. (Frontiers in Rehabilitation Sciences, 2021)
The twenty-first century has seen an increase in para-sport participation and the number of research publications on para-sport and the para-athlete. Unfortunately, the majority of publications are case reports/case series or study single impairment types in isolation. Indeed, an overview of how each International Paralympic Committee classifiable impairment type impact athlete physiology, health, and performance has not been forthcoming in the literature. This can make it challenging for practitioners to appropriately support para-athletes and implement evidence-based research in their daily practice. Moreover, the lack of a cohesive publication that reviews all classifiable impairment types through a physiological lens can make it challenging for researchers new to the field to gain an understanding of unique physiological challenges facing para-athletes and to appreciate the nuances of how various impairment types differentially impact para-athlete physiology. As such, the purpose of this review is to (1) summarize how International Paralympic Committee classifiable impairments alter the normal physiological responses to exercise; (2) provide an overview of ‘quick win’ physiological interventions targeted towards specific para-athlete populations; (3) discuss unique practical considerations for the para-sport practitioner; (4) discuss research gaps and highlight areas for future research and innovation, and (5) provide suggestions for knowledge translation and knowledge sharing strategies to advance the field of para-sport research and its application by para-sport practitioners.